The different release techniques in high level archery: a comparative case study - Simsek, D.; Ertan, H. (ISBS - Conference Proceedings Archive (Konstanz), 2014)
Olympic archers use different hook techniques like upper and lower two-finger hook. So, the purpose of this study is to compare three different hook techniques in archery by using kinetic and kinematic methods. A high level archer (FITA scores > 1300) volunteered to participate in this study. The subject engaged in a single test session consisting of 6 shots. Nine forearm and shoulder girdle muscles activation were quantified. The finger hook affected isometric contraction before the snap of the clicker causing sudden contraction of extensors and gradual relaxation of flexor muscles. This finding support earlier finding in the literature. Results showed that three finger hook strategy can be used in the drawing arm with success, as it may avoid causing a lateral deflection of the bowstring.